Giant angiokeratoma of fordyce over the vulva in a middle-aged woman: Case report and review of literature - Mohan H Kudur; Manjunath Hulmani (Wolters Kluwer Medknow Publications, 2013)
Angiokeratoma of Fordyce occurring over vulva is rare. Angiokeratoma of Fordyce commonly occurs in males over scrotum or penile shaft and presents as multiple verrucous reddish papules. They are usually asymptomatic and noticed accidentally. In the present article, we present and review the literature of giant angiokeratoma of Fordyce in middle-aged women due to its rarity.